The Victimized Personas in Jean Rhys’s Wide Sargasso Sea and Charlotte Bronte’s Jane Eyre, Feminism Perspectives - Hayder M. Saadan M. Ridha AL-Hasani (Randwick International of Education and Linguistics Science Journal, 2023)
The Wide Sargasso Sea - (1966). After years of contemplating Charlotte Bronte's Creole madwoman Bertha Mason, Jean Rhys set out to give voice to what is mute in Bronte’s Jane Eyre. Rhys lets Antoinette narrate her tale, revealing the "other side" of Bronte's story: what occurred in the years before and after Mr. Rochester's first marriage in Jamaica. As a twentieth-century West Indian writer, Rhys was able to expose implicit assumptions and ideals in Bronte's writing, such as imperialist England's attitude toward her colonies. The natural environment is a mirror of interior states of being and emotion, a remark on the novel's characterization and action. Even though the two books seem to be identical, they are not. Rhys flips Bronte's Victorian Romantic symbols, Wide Sargasso Sea appears more contemporary and realistic. This paper aims to highlight the victimized characters in both novels and gives a real comparison of the most victimized ones. Both works, respectively, show women fighting patriarchy and injustice at any historical time. From a feminist standpoint, this study compares, Bertha Mason, in the two narratives. Even though Wide Sargasso Sea is a forerunner to Jane Eyre, Rhys expressed a more progressive and revolutionary feminist viewpoint. Bertha Mason is a more victimized female than Jane of the patriarchal system and colonization. These feminist works have left an indelible effect on literature. Most literary commentators have concentrated on Jane, the protagonist of Charlotte Bronte's narrative, on the other hand, there is Bertha Mason, the insane lady on the upper floor imprisoned, as just Jane's evil twin. Bertha has received much less attention than Jane, not as an evil side of Jane, but as a stand-alone figure. This study compares Bertha Mason's representation in Jane Eyre and Wide Sargasso Sea. Bertha, who acts as an impediment to Jane's pleasure in Jane Eyre, is recognized as a victim of society.